Privacy and Security of Cloud Computing: A Comprehensive Review of Techniques and Challenges - Adnan Darwish, Marwan; Yafi, Eiad; H. Almasri, Abdullah; F Zuhairi, Megat (International Journal of Engineering and Technology, 2018)
Cloud computing usage is rapidly increasing in a various range of services and it is seen on trend to revolutionize the way the IT companies doing businesses. The recent advances in mobile, social media companies and online businesses have given rise to success and propagation for the environment of the cloud. However, When uploading the users' data from the local device to the nature of the cloud that considered as a third party , major challenges cloud-computing model jeopardizes privacy and security issues and threats on data security and reliability. These threats constitute data breaches, loss of control, unauthorized uses at the different layers of the cloud models and these issues hinder the adoption of cloud and slow down acceptance in many sectors in IT. In this review, we present and summarize major articles in cloud computing and its multiple layers with a focus on security and privacy challenges (such as integrity, confidentiality and data privacy). We also intend to review the latest approaches regarding identity management inside the cloud, cryptography and steganography techniques that have been used inside the cloud platforms.Â